Dropout in youth and adult education: a multilevel analysis of students and schools in Chile - Contreras-Villalobos, Tabata; López, Verónica; Baleriola, Enrique; González, Luis (Frontiers in Psychology, 2023)
Introduction School dropout is an increasing worldwide phenomenon, marked by inequality and educational exclusion. In Chile, many students who have dropped out of regular schools attempt to reenter youth and adult education (YAE). However, some of them drop out again from YAE. Objective The aim of this study was to identify and jointly analyze school and individual factors that influence dropout in YAE. Methods This secondary multilevel analysis of official datasets from Chile’s Ministry of Education focused on students enrolled in YAE (N = 10,130). Results According to the findings, YAE dropout can be explained by the individual risk factors of age (19–24 years), low academic achievement, and school-level factors such as number of teachers (raw and student-to-teacher ratio), economic resources, and school management quality. Discussion We discuss the need to develop school-level protective factors that build connections, foster student engagement, and ultimately, promote students’ permanence and progress in YAE.